Defective DNA Replication Impairs Mitochondrial Biogenesis In Human Failing Hearts Karamanlidis: Mitochondrial biogenesis in human heart failure - Karamanlidis, Georgios (2010)
RATIONALE: Mitochondrial dysfunction plays a pivotal role in the development of heart failure. Animal studies suggest that impaired mitochondrial biogenesis due to down-regulation of the PGC-1 transcriptional pathway is integral of mitochondrial dysfunction in heart failure. OBJECTIVE: The study sought to define mechanisms underlying the impaired mitochondrial biogenesis and function in human heart failure. METHODS AND RESULTS: We collected left ventricular (LV) tissue from end-stage heart failure patients and from non-failing hearts (n = 23, and 19, respectively). The mitochondrial DNA (mtDNA) content was decreased by >40% in the failing hearts, after normalization for a moderate decrease in citrate synthase activity (p<0.05). This was accompanied by reductions in mtDNA-encoded proteins (by 25%–80%) at both mRNA and protein level (p<0.05). The mRNA levels of PGC-1α/β and PRC were unchanged while PGC-1α protein increased by 58% in the failing hearts. Among the PGC-1 co-activating targets, the expression of ERRα and its downstream genes decreased by up to 50% (p<0.05) while PPARα and its downstream gene expression were unchanged in the failing hearts. The formation of D-loop in the mtDNA was normal but D-loop extension, which dictates the replication process of mtDNA, was decreased by 75% in the failing hearts. Furthermore, DNA oxidative damage was increased by 50% in the failing hearts. CONCLUSIONS: Mitochondrial biogenesis is severely impaired as evidenced by reduced mtDNA replication and depletion of mtDNA in the human failing heart. These defects are independent of the down-regulation of the PGC-1 expression suggesting novel mechanisms for mitochondrial dysfunction in heart failure.